Accountability and Political Responsiveness in Local Legislatures: A Case Study of the Sleman Regency DPRD - Surana, Surana (Saneskara: Journal of Social Studies, 2025)
This study examines the effectiveness of the core functions of the Regional People’s Representative Council (DPRD) of Sleman Regency—legislation, budgeting, and oversight—within the framework of local governance and political accountability. Despite a clear legal mandate, the DPRD’s practical performance often reveals a discrepancy between normative expectations and administrative realities. Using a qualitative case study design, data were collected through in-depth interviews with DPRD members, secretariat officials, and civil society representatives, complemented by participant observation and document analysis of legislative outputs and performance reports. Purposive sampling and data triangulation ensured analytical depth and validity. Findings indicate that the DPRD of Sleman Regency has demonstrated progress in legislative productivity and budgetary planning, evidenced by the enactment of five key local regulations in 2024 and the proposal of twelve priority drafts in 2025. However, the council’s effectiveness remains constrained by uneven member capacity, limited substantive public participation, weak follow-up mechanisms, and inadequate institutional support, while local political dynamics continue to shape its responsiveness and accountability. The study concludes that strengthening DPRD performance requires continuous professional development, transparent digital information systems, and structured participatory mechanisms. Although this research focuses on a single regional case, it offers valuable insights into the socio-institutional factors influencing local legislative effectiveness in Indonesia and provides a foundation for comparative studies across regional parliaments.